2020
DOI: 10.1002/jia2.25582
|View full text |Cite
|
Sign up to set email alerts
|

Differences in HIV risk and healthcare engagement factors in Filipinx transgender women and cisgender men who have sex with men who reported being HIV negative, HIV positive or HIV unknown

Abstract: Introduction Understanding HIV risk and healthcare engagement of at‐risk individuals by HIV status is vital to informing HIV programmes in settings where the HIV epidemic is rapidly expanding like the Philippines. This study examined differences in HIV risk and healthcare engagement factors among Filipinx transgender women and cisgender men who have sex with men (trans‐WSM and cis‐MSM respectively) who self‐reported being HIV negative, HIV positive or HIV unknown. Methods Between 2018 and 2019, we conducted Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, the Integrated HIV Behavioral and Serologic Surveillance embedded in the Health Sector Plan for HIV and STI 2015 to 2020 of the Philippine Department of Health (DOH), an active sentinel serologic and behavioral surveillance, suggested actions to increase HIV and HIV-related services both for the TG and men-having-sex-with-men (MSM) populations [43,44]. However, the guidelines for the increase in uptake of HTC services among the TW and TM should be further strengthened because of the existing barriers to testing [45]. Our study aimed to identify gender identity as a factor that enables the TG populations to refuse or decline HIV testing services.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Integrated HIV Behavioral and Serologic Surveillance embedded in the Health Sector Plan for HIV and STI 2015 to 2020 of the Philippine Department of Health (DOH), an active sentinel serologic and behavioral surveillance, suggested actions to increase HIV and HIV-related services both for the TG and men-having-sex-with-men (MSM) populations [43,44]. However, the guidelines for the increase in uptake of HTC services among the TW and TM should be further strengthened because of the existing barriers to testing [45]. Our study aimed to identify gender identity as a factor that enables the TG populations to refuse or decline HIV testing services.…”
Section: Discussionmentioning
confidence: 99%
“…However, the guidelines for the increase in uptake for HTC services among the TW and TM should be further strengthened because of the existing barriers to testing. [33] Our study aimed to identify the factors that enable the TG populations to refuse or decline HIV testing services. Through medical records review, our study showed that most TM did not consent or accept HIV testing services from the VLY, and they are more likely to refuse HIV testing services compared to TG.…”
Section: Discussionmentioning
confidence: 99%
“…Of the total reported new HIV cases in January 2023, 3% were transgender women [ 5 ]. Unique concerns among transgender populations in the Philippines include differences in HIV knowledge, need for safe sex communication, and disparate access to healthcare services [ 17 ]. One study among trans men and trans women ( N = 525) in Metro Manila showed that as many as 82% declined HIV testing and counseling services [ 18 ].…”
Section: Populations Disproportionately Impacted By Hivmentioning
confidence: 99%